2018
DOI: 10.3904/kjim.2016.067
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of living donor kidney transplantation in diabetic patients: age and sex matched comparison with non-diabetic patients

Abstract: Background/AimsKidney transplantation (KT) reportedly provides a significant survival advantage over dialysis in diabetic patients. However, KT outcome in diabetic patients compared with that in non-diabetic patients remains controversial. In addition, owing to recent improvements in the outcomes of KT and management of cardiovascular diseases, it is necessary to analyze outcomes of recently performed KT in diabetic patients.MethodsWe reviewed all diabetic patients who received living donor KT between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
12
1
1
Order By: Relevance
“…We detected that infection was more often coded in people without diabetes, except for kidney transplant, and graft complications were more frequent among people without diabetes for all types of transplants. Both older and recent reports describe a higher short‐term infection rate after kidney transplant in people with type 2 diabetes, too . However, we do not have straightforward explanations for the rest of the findings.…”
Section: Discussioncontrasting
confidence: 71%
“…We detected that infection was more often coded in people without diabetes, except for kidney transplant, and graft complications were more frequent among people without diabetes for all types of transplants. Both older and recent reports describe a higher short‐term infection rate after kidney transplant in people with type 2 diabetes, too . However, we do not have straightforward explanations for the rest of the findings.…”
Section: Discussioncontrasting
confidence: 71%
“…However, Baek et al assessed clinical outcomes after living donor kidney transplantation in patients with diabetes compared to non-diabetic patients. The incidence of acute rejection, death-censored graft failure, non-death-censored graft failure, and mortality were not significantly different between patients with and without diabetes after living donor kidney transplantation [26]. Nevertheless, we are aware of this limitation in our study, and a well-designed prospective clinical trial is needed to assure accurate randomization and minimize the effect of such clinical variables on the clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Baek et al [28] reported that there were no significant changes in the rates of rejection between diabetic and non-diabetic recipients. Some authors suggested that patients with diabetes were rendered susceptible to cellular rejection because of their significant risk of exacerbation of glycemic control after transplantation and that strict glycemic control might be important [4, 28]. In this study, glycemic control was relatively good because of the less than 7.0% HbA1c levels, which the Japan Diabetes Society recommends in order to avoid diabetic complications.…”
Section: Discussionmentioning
confidence: 99%